Barriers to Accessing Health Care in Rural Regions by Transgender, Non-Binary, and Gender Diverse People: A Case-Based Scoping Review - Renner, Janis; Blaszcyk, Wiebke; Täuber, Lars; Dekker, Arne; Briken, Peer; Nieder, Timo O. (Frontiers in Endocrinology, 2021)
Research shows an overrepresentation of trans people in vulnerable socioeconomic situations, primarily due to experiences of discrimination. At the same time, rural or suburban living areas often lack specialized trans-related health care, which a majority of trans people rely on to some extent. Taken together, the lack of both socioeconomic resources and access to trans-related health care can exacerbate health-related distress and impairment for trans people. We illustrate this problem using case vignettes of trans people from rural and suburban areas in (Northern) Germany. They are currently participating in an e-health intervention and randomized controlled trial (RCT) called i2TransHealth, whose case vignettes provided the impetus for the scoping review. The scoping review analyzes the impact of place of residence and its intersection with barriers to accessing trans-related health care. PubMed and Web of Science Data bases were searched for relevant studies using a search strategy related to trans people and remote, rural, or suburban residences. 33 studies were selected after full-text screening and supplemented via reference list checks and study team expertise by 12 articles addressing the living conditions of remotely living trans people and describing requirements for trans-related health care. The literature on trans people living remotely reveals intersections of trans mental health with age, race, gender expression, geographic location, community size, socioeconomic status, discrimination experiences, and attitudes towards health care providers. Several structural health care barriers are identified. The role of health care professionals (HCPs) for remotely living trans people is discussed. There is no need assuming that rural life for trans people is inevitably worse for health and well-being than urban life. Nevertheless, some clear barriers and health disparities exist for trans people in remote settings. Empowering trans groups and diversity-sensitive education of remote communities in private and institutional settings are needed for respectful inclusion of trans people. Facilitating access to trans-related health care, such as through video-based e-health programs with HCPs, can improve both the health and socioeconomic situation of trans people.